Water’s role in ensuring food security: An analysis of Malaysia from 1991 to 2020 - Yeoh, Rachel Sue Yeen; Wong, Kar Yee (2024)
Food security has been a prominent economic issue in the world which is gradually gaining global attention, especially climate change, population growth and socio-economic disparities has been a global challenge these days. Undoubtedly food security has emerged as a pressing issue worldwide. The COVID-19 pandemic has further intensified existing vulnerabilities in food systems, highlighting the urgent need for resilient and sustainable approaches to ensure adequate food supply for all. This study aims to analyze the relationship between water resources, economic growth (economical aspect), population growth (social aspect), carbon dioxide emission (environmental aspect) and food security in Malaysia over the period from 1991 to 2020. Moreover, there are 3 prominent theories supporting our study, namely, Keynesian Theory, Neo-Malthusian Theory, and Photosynthesis Theory. Water resources will serve as our focus in this study. Data of all independent variables was collected from international sources - World Bank Data. Statistical analysis including Unit Root Test, ARDL Cointegration Bounds Test, Error Correction Model, ARCH Test, LM Test, CUSUM Test, VIF Test, and Normality Test was employed in this study. The findings indicate a significant positive correlation between water resources and food security indicators in Malaysia over the period of 1991 - 2020